Konstruksi Sosial Atas Pemaknaan Dan Simbol Kecantikkan Pada Trending Hastag Tik Tok - Andi Setyawan (Risenologi, 2021)
Reality is only a social construction created by humans. Tik Tok is a new reality phenomenon constructed by the community as a form of self-expression. One of the features offered by Tik Tok is trending hashtag, which is a collection of the most popular videos. The number of Tik Tok users, especially women, are competing to create content related to the meaning of beauty. This study seeks to analyze the social construction of the meaning of the symbol of beauty in the trending hashtag Tik Tok. The samples of this study were 4 trending hashtags, namely: ladadida challenge, negligee challenge, dualism challenge and ah steady challenge. By using the Zhongdang Pan and Gerald M. Kosicki's framing analysis, the results show that there are beauty constructs from these 4 challenges. The symbol of beauty on Tik Tok proves that those users with beautiful faces, white, make up, and wear good clothes are those who are popular and get a lot of attention from other users. The results of this study are expected to be able to be used as literacy for the younger generation, especially Tik Tok social media users, to be wiser in constructing beauty, that everyone is basically beautiful and has different standards of beauty.